Indústria cultural e educação : o youtube como espaço de manifestação e mediação das tensões na escola - Ferraro, Joênia Ricarte (2012)
This study has as purpose an analysis of relational tensions and the way they are present into schools, including among them, the relationship that is established between teachers and students a full of meanders and veiled messengers interaction. Fruit of social tensions generated and perpetuated by a manipulator process of production, the dialogue between teachers and students reaches the highest point in episodes of mutual aggression, destruction of the self esteem and in a detachment of the intended goals. Inserted in a complex reality that favors the mass production and consume, fed by ideologies, the educational processes are marked by difficulties to fulfill his role of former human beings able to exercise their role as citizens, as recommended by laws, statutes and declarations that focus the educational question. The influence of the cultural industry in education is one of the central focuses of this study; as well the reflex of massification and of the resentment that comes of this and that is manifested in the school environment. Scenes that show episodes of disagreements and aggressiveness between students and teachers were recorded by students in classrooms and were, here analyzed under the Critical Theory optics to glimpse the panorama in which the educational process are developed and the solutions that theorists present to go beyond the capital by a more humanized education that wins the barbarism nowadays installed.